(3GdTjN eMeO Rci EHQGgje (B( 1906 (3e (B/ 1998(3e (B) (3hefgLg ai GdEUdGM(B/ s - (3efi eMeO eMehO CMeOs; (3YHOGdMejO YHOGdefYe eOchQ (B: s ((3GdbGgQI (B: s (3efi eMeO eMehO CMeO (B: s, 2012)
(3JfGhd GdHMK TNUjI UhajI eYGUQI cGf dgG LgO hGVM ai GdEUdGM HYGeI hGdEUdGM GdUhai NGUI hgh aVjdI GdTjN eMeO Rci EHQGgje TjN GdWQjbI GdeMeOjI GdTGPdjI hbO GYJeO GdefgL GdQhMi ai GdEUdGM hfGOi HVQhQI HfGA GdEfSGf bHd GdHfjGf eJcFG Ydi CNU eG jejR GdEfSGf CdG hgh YdGbJg HNGdbg SHMGfg eHjfG Cf HfGA gPg GdYdGbI hJbhjJgG EfeG gPg GdYdGbI hJbhjJgG EfeG jchf ef NdGd QcjRJjf CSGSjJjf JeKdGf GdLfGMjf GdYedjjf ddJUha CdG hgeG GdYHGOI hGdaVjdI eDcOG Ydi Cf JbhjI gPg GdYdGbI gi CSGS UdGM GdaQO GdPi JUdM HUdGMg GdLeGYI cdgGs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQGdYdhe (B- (3bSe GdadSaI GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdEUdGM s; (3GdJUha s; (3GdYHGOI s